Sphingosine 1-phosphate receptor modulation suppresses pathogenic astrocyte activation and chronic progressive CNS inflammation - Rothhammer, Veit; Kenison, Jessica E.; Tjon, Emily; Takenaka, Maisa C.; De Lima, Kalil Alves; Borucki, Davis M.; Chao, Chun-Cheih; Wilz, Annabel; Blain, Manon; Healy, Luke; Antel, Jack; Quintana, Francisco J. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Multiple sclerosis (MS) is an autoimmune inflammatory demyelinating disease of the CNS that causes disability in young adults as a result of the irreversible accumulation of neurological deficits. Although there are potent disease-modifying agents for its initial relapsing-remitting phase, these therapies show limited efficacy in secondary progressive MS (SPMS). Thus, there is an unmet clinical need for the identification of disease mechanisms and potential therapeutic approaches for SPMS. Here, we show that the sphingosine 1-phosphate receptor (S1PR) modulator fingolimod (FTY720) ameliorated chronic progressive experimental autoimmune encephalomyelitis in nonobese diabetic mice, an experimental model that resembles several aspects of SPMS, including neurodegeneration and disease progression driven by the innate immune response in the CNS. Indeed, S1PR modulation by FTY720 in murine and human astrocytes suppressed neurodegeneration- promoting mechanisms mediated by astrocytes, microglia, and CNS-infiltrating proinflammatory monocytes. Genome-wide studies showed that FTY720 suppresses transcriptional programs associated with the promotion of disease progression by astrocytes. The study of the molecular mechanisms controlling these transcriptional modules may open new avenues for the development of therapeutic strategies for progressive MS.
CRIS-Team Scopus Importer:2020-09-22
Keywords: Astrocytes; Eae; Multiple sclerosis; Secondary progression; Sphingolipid metabolism